Системный анализ и математические методы оценки экономической эффективности управления региональными промышленными комплексами (Путеводитель предпринимателя, 2020)
Problems the basic problems of an estimation of management efficiency are considered by the enterprises entering into a regional industrial complex on the basis of an estimation of each made decision from the point of view ofpossibility of extraction of benefit.